Perancangan Card Game Kue Tradisional Indonesia Untuk Usia 18 – 21 Tahun (Pixel :Jurnal Ilmiah Komputer Grafis, 2025)
This research presents the design of a card game titled "Kejutan Manis Nusantara", aimed at introducing traditional Indonesian cakes to Generation Z, particularly those aged 18 to 21, in a fun and interactive way. This game combines education about the richness of Indonesian cuisine with a social experience that strengthens relationships among players. The card game design implements semi-realistic illustrations that clearly depict the cakes, making it easy for players to recognize traditional Indonesian cakes. The results of this research are expected to contribute to the preservation of Indonesian culture, especially in the culinary field, while introducing the diversity of Indonesian traditional cakes to the younger generation in an engaging way